Novel Visualization Methods Assisted Transurethral Resection for Bladder Cancer: An Updated Survival-Based Systematic Review and Meta-Analysis - Li, Honglin; Cao, Yubin; Ma, Pingchuan; Ma, Zhongkai; Li, Chunjie; Yang, Wenbin; Zhou, Lingyun (Frontiers in Oncology, 2021)
Background: Photodynamic diagnosis and narrow-band imaging could help improve the detection rate in transurethral resection (TUR) of bladder cancer. It remained controversial that the novel visualization method assisted transurethral resection (VA-TUR) could elongate patients’ survival compared to traditional TUR. Methods: We performed electronic and manual searching until December 2020 to identify randomized controlled trials comparing VA-TUR with traditional TUR, which reported patients’ survival data. Two reviewers independently selected eligible studies, extracted data, assessed the risk of bias. Meta-analysis was conducted according to subgroups of types of visualization methods (A) and clinical stage of participants. Publication bias was detected. Results: We included 20 studies (reported in 28 articles) in this review. A total of 6062 participants were randomized, and 5217 participants were included in the analysis. Only two studies were assessed at low risk of bias. VA-TURB could significantly improve the recurrence-free survival (RFS) (HR=0.72, 95% CI: 0.66 to 0.79, P<0.00001, I2=42%) and progression-free survival (PFS) (HR=0.62, 95% CI: 0.46 to 0.82, P<0.0008, I2=0%) compared with TUR under white light. The results remain stable whatever the type of visualization method. The difference could be observed in the non-muscle-invasive bladder cancer (NMIBC) population (P<0.05) but not in the mixed population with muscle-invasive bladder cancer (MIBC) participants (P>0.05). Conclusion: VA-TUR could improve RFS and PFS in NMIBC patients. No significant difference is found among different types of VA-TUR. VA-TUR may be not indicated to MIBC patients.